Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s00280-009-0946-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of feasibility and toxicity of concurrent chemoradiotherapy with S-1 for locally advanced squamous cell carcinoma of the head and neck in elderly cases and/or cases with comorbidity

Abstract: Purpose The aim of this study was to evaluate the feasibility and toxicity of concurrent chemoradiotherapy (CCRT) with S-1 in patients with locally advanced squamous cell carcinoma of the head and neck (SCCHN) in elderly cases and/or cases with comorbidity. Methods Fifty eligible patients with stage III (15 cases) or stage IV (35 cases) SCCHN were treated with CCRT. Thirteen cases had an advanced age of over 75 years and 37 cases had comorbidity. Definitive radiotherapy was delivered up to a total dose of 66-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Preliminary clinical studies have demonstrated the potential efficacy of chemoradiotherapy with S-1 and radiation in treating locally advanced head and neck and pancreatic cancers (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary clinical studies have demonstrated the potential efficacy of chemoradiotherapy with S-1 and radiation in treating locally advanced head and neck and pancreatic cancers (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Sato et al reported that the RD of S-1 was 65 mg/m 2 /day when radiation was given to a total dose of 60 Gy and S-1 was administered every day for 2 weeks and then was suspended for 1 week [16]. In addition, Tsukuda et al reported that the RD of S-1 was 80-100 mg/body/day when radiation was given to a total dose of 60-70.2 Gy, and S-1 was administered every day for 2 weeks and was then suspended for 1 week [17]. Furthermore, Harada et al reported the results of an S-1 dose escalation study that had almost the same schedule as our study.…”
Section: Discussionmentioning
confidence: 99%
“…The difference from our study is that their total radiation dose was only 40 Gy because they were giving preoperative concurrent chemoradiotherapy. There have been other reports on Phase III trials of radiotherapy with S-1 [19][20][21][22][23] or the combination of S-1 and cisplatin/nedaplatin [24][25][26] for head and neck cancer. These studies have demonstrated that S-1 and concurrent radical radiotherapy is safe and well tolerated by patients with complications and is a patient-friendly treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports about the administration of S-1 as adjuvant chemotherapy for head and neck cancer. One report recommended that S-1 should be administered at a dose of 60 mg/m 2 /day for 5 days, followed by 2 days off, in combination with irradiation (total dose: 64-70 Gy) for 6-7 weeks [12], while another study recommended that S-1 should be administered every day at a dose of 80-100 mg/body/day for 2 weeks and then suspended for 1-2 weeks to allow radiotherapy to be performed (total dose: 60-70.2 Gy) [13,14]. On the basis of the results of these studies, we chose a treatment regimen in which S-1 was delivered at a dose of 80 mg/body/day every day for 2 weeks before surgery.…”
Section: Discussionmentioning
confidence: 99%